2005
DOI: 10.1111/j.1525-139x.2005.18410.x
|View full text |Cite
|
Sign up to set email alerts
|

ASDIN Clinical Case Focus: Retrieval of a Fractured Piece of Tessio Catheter with a Snare Using a Transcutaneous Transvenous Approach

Abstract: Approximately 20% of end-stage renal disease patients requiring hemodialysis have central dialysis catheters as their vascular access. The major cause of central dialysis catheters removal or revision is infection or occlusion. Catheter occlusions may occur as a result of thrombosis or fibrin sheath formation. However, the presence of a fractured dialysis catheter tip requiring immediate extraction to prevent serious complications is rare. Herein we present the case of a central dialysis catheter referred to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Inappropriate use of metal instruments, such as needles, probes, scalpel blades, and catheters (Bump and Roche, 1973;Bedrock et al, 1999;Prasad et al, 2000;Miura et al, 2001;Oztekin, 2005;Zaman et al, 2005;Ma et al, 2006), can result in their breakage during surgery. These are then capable of moving to an unexpected site in soft tissue or interfering with further treatment procedures, like tooth extractions and implant placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate use of metal instruments, such as needles, probes, scalpel blades, and catheters (Bump and Roche, 1973;Bedrock et al, 1999;Prasad et al, 2000;Miura et al, 2001;Oztekin, 2005;Zaman et al, 2005;Ma et al, 2006), can result in their breakage during surgery. These are then capable of moving to an unexpected site in soft tissue or interfering with further treatment procedures, like tooth extractions and implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…An intrapulmonary aberrant needle was removed under fluoroscopic guidance to avoid re-thoracotomy (Miura et al, 2001), and symptomatic bone anchors placed during stress incontinence surgery were successfully removed, along with surrounding bone, with fluoroscopy (Stoffel et al, 2005). Zaman et al (2005) reported retrieval of broken dialysis catheters under fluoroscopic guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases have been reported in recent literature showing the difficulties encountered in the retrieval of catheters that were used for long term and a fibrin sheath wraps the catheter along its trajectory. [4][5][6][7]…”
Section: Discussionmentioning
confidence: 99%
“…Migration of portions of central catheters has been described in the past, with retrieval from the cavae[ 8 ], right atrium[ 9 ], right ventricle[ 10 ], and pulmonary arteries[ 11 ]. Although many patients, such as this one, have remained asymptomatic[ 12 ], migration of catheters has been associated with serious complications such as pulmonary embolism with subsequent pulmonary infarction[ 13 ], myocardial or pulmonary parenchymal perforation[ 14 ] and palpitations and arrhythmias[ 15 ].…”
Section: Discussionmentioning
confidence: 99%